Implementasi Prestashop Pengembangan Website Hingga Pemasaran Dan Logistik Pada Toko SS Galery Rantauprapat - Juwita, Juwita; Harahap, Syaiful Zuhri; Bangun, Budianto (Universitas Labuhanbatu, 2024)
This article discusses the implementation of PrestaShop in website development, marketing and logistics at the SS Galery Rantauprapat store. PrestaShop is an e-commerce platform designed to make it easier to create and manage online stores with features that support sales, including product management, payment systems, and sales analysis. In the context of SS Gallery, the implementation of PrestaShop aims to increase operational efficiency and expand market reach. The implementation process begins with designing a website that is responsive and user-friendly, allowing customers to access product information easily. The e-marketing features in PrestaShop are also used to increase product promotions, attract more customers and increase their loyalty. In addition, an integrated logistics system helps in managing goods delivery efficiently, reducing customer waiting time. The results of this research show that using PrestaShop not only increases sales productivity but also simplifies the marketing process and logistics management. In this way, SS Galery Rantauprapat can compete better in an increasingly competitive digital market. This research provides insight for other business actors about the importance of information technology in supporting business growth in the digital era.